Saphenocavernous shunt in the treatment of priapism - Mazza, Milton; Crestanello, Francisco; Castiglioni, Juan A; Schenone, Héctor; García, Luis (Cirugía del Uruguay, 1973)
A safeno-cavernous by-pass was performed as treatment of idiopathic priapism. It proved effective in control of acute situation. No further erections ocurred.